Foreword - Reichlin, Seymour (Acta Biomedica Atenei Parmensis, 2007)
Imagine if you will a two or three day informal meeting in Emilia-Romagna, Italy, in which a group of scientists, mostly endocrinologists, with an admixture of immunologists, neuroscientists, mathematicians, theoretical biologists and philosophers of science have a chance to tell one another about their pet ideas, speculations, and cutting edge research into a wide variety of subjects...